Evaluation of MRI Findings in Tension Type Headache Patients - SC Sanjay; Harshavardhan; Meraj (Asian Journal of Medical Radiological Research, 2020)
Background: Tension-type headache (TTH) has a life-time prevalence of up to 78% in the general population. It is characterized by bilateral location, pressing/tightening quality and is typically of mild to moderate intensity. Hence; the present study was conducted for evaluation of MRI findings in tension type headache patients. Subjects and Methods: A total of 12 patients with tension type headache were enrolled. Complete demographic details of all the patients were recorded. Relevant history, clinical examination and routine investigations were done. Patients underwent MRI investigations. MR imaging findings were compiled as per proforma and subjected to analysis using SPSS software. Chi-square test was used for assessment of level of significance. Results: Significant abnormal MRI findings were found to be present in 1 patient with tension type headache. The patients with significant MRI finding showed few small discrete T2 and T2 flair Hyperintensities in subcortical white matter. Conclusion: Patients with tension type headache should be viewed with suspicion and MRI should be done for excluding other potential etiologic factors.